Konstruksi Penalaran Statistis pada Statistika Penelitian - Yusfita Yusuf (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2017)
Statistics can be viewed as a tool to solve problems that always occur in everyday life,workplace, and science. Based on the observation on the students, it was found that the there was statistical reasoning abilities of different students. This could be demonstrated by the acquisition of the different test scores, in which there were students who just copy the questions until finishing the work on the problems given. This study discussesed the development deduction level / degree of statistical reasoning skills based on understanding and opinion of several experts, which were constructed based on the results of a case study of mathematics education on STKIP students of Sebelas April Sumedang with statistical research material.